A comparison of the efficacy, safety, and longevity of two different hyaluronic acid dermal fillers in the treatment of severe nasolabial folds: a multicenter, prospective, randomized, controlled, single-blind, within-subject study - Rogers JD; Halstead MB; Rosen RH; Rich M; Bekhor P; Goodman GJ (Dove Medical Press, 2011)
Greg J Goodman1, Phillip Bekhor2, Michael Rich3, Robert H Rosen4, Michael B Halstead5, John D Rogers51Dermatology Institute of Victoria, South Yarra, Victoria, Australia; 2Laser Dermatology, Box Hill, Victoria, Australia; 3enRich Dermatology and Cosmetic Surgery Centre, Armadale, Victoria, Australia; 4Southderm Pty Ltd, Kogarah, New South Wales, Australia; 5Allergan Australia, Gordon, New South Wales, AustraliaBackground: Commercially available hyaluronic acid (HA)-based fillers have distinct physicochemical properties related to their specific manufacturing technology, including HA concentration, cross-linking percentage, and particle size. These factors may determine treatment effectiveness, safety, and longevity; however, this requires confirmation in the clinic.Methods: To compare the efficacy, safety, and longevity of two distinct HA-based dermal fillers in the correction of severe nasolabial folds (NLFs), a 24 mg/mL smooth gel (Juvederm ULTRA PLUS™ [JUP]) and a 20 mg/mL particulate gel (Perlane® [PER]) were injected in a total of 80 normal, healthy subjects using a split face design and were followed for 12 months in this prospective, randomized, controlled, multicenter study.Results: Both fillers achieved a clinically relevant NLF correction (one point or more improvement, based on a validated NLF severity scale). However, JUP displayed greater longevity, with this correction maintained in a significantly larger percentage of NLFs after 6 months (physician's evaluation) or 9 months (subject's evaluation) and thereafter for the remainder of the study (70% vs 45%; P = 0.0002 and 62.5% vs 46.3%; P = 0.01 at month 12, based on physician and subject assessments, respectively). At month 12, 71.4% of the subjects nominated a preference for the NLF injected with JUP (P < 0.0001). Both treatments were well tolerated.Conclusion: These results suggest that different physicochemical properties of HA-based fillers, associated with distinct manufacturing technologies, may influence treatment longevity in the correction of volume deficits. This may relate to a differential resistance to hyaluronidase and/or free radical degradation as previously documented in vitro.Keywords: hyaluronic acid, dermal fillers, volume deficit, nasolabial folds, randomized, controlled